The use of neutron scattering to determine the functional structure of glycoside hydrolase. (October 2016) - Nakamura, Akihiko; Ishida, Takuya; Samejima, Masahiro; Igarashi, Kiyohiko
Graphical abstract: Highlights: Advantages and difficulties of neutron crystallography were discussed. Protonation state of catalytic residues can be determined. Hydrogen bond network mediated by water molecules was determined. Proton pathway in cellulase was observed. Abstract : Neutron diffraction provides different information from X-ray diffraction, because neutrons are scattered by atomic nuclei, whereas X-rays are scattered by electrons. One of the key advantages of neutron crystallography is the ability to visualize hydrogen and deuterium atoms, making it possible to observe the protonation state of amino acid residues, hydrogen bonds, networks of water molecules and proton relay pathways in enzymes. But, because of technical difficulties, less than 100 enzyme structures have been evaluated by neutron crystallography to date. In this review, we discuss the advantages and disadvantages of neutron crystallography as a tool to investigate the functional structure of glycoside hydrolases, with some examples.